2010
DOI: 10.1111/j.1440-1789.2010.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain pathology in fatal serotonin syndrome: Presentation of two cases

Abstract: Serotonin syndrome is a potentially life-threatening reaction that occurs in patients using drugs that elevate the serotonin level in the body. Excess serotonergic activity in the CNS and peripheral serotonin receptors results in neuromuscular hyperactivity, mental changes and autonomic symptoms. Hyperthermia is a characteristic feature of the syndrome. We describe neuropathological findings from two cases of lethal serotonin syndrome, both patients presenting with hyperthermia and neuromuscular symptoms. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…This finding was postulated by several investigators to reflect the effects of hyperthermia rather than any underlying pathophysiology of NMS [73,75]. Slettedal et al demonstrated similar findings in two patients with the serotonin syndrome [76]. Similar cerebellar changes have been demonstrated on autopsy in patients with severe hyperthermia from other causes [75].…”
Section: Postmortem Changessupporting
confidence: 62%
“…This finding was postulated by several investigators to reflect the effects of hyperthermia rather than any underlying pathophysiology of NMS [73,75]. Slettedal et al demonstrated similar findings in two patients with the serotonin syndrome [76]. Similar cerebellar changes have been demonstrated on autopsy in patients with severe hyperthermia from other causes [75].…”
Section: Postmortem Changessupporting
confidence: 62%
“…Studies in experimental animals have indicated that a slight elevation of serotonin levels decreases body temperature through neural transmission involving the 5-HT1A receptors, whereas the considerable elevation of serotonin levels induces high body temperature through 5-HT2A neural transmission 14,15. Therefore, it could be hypothesized that while a slight excess of serotonin causes side effects by activating the 5-HT1A receptor, a significant increase in serotonin levels can induce lethal side effects with hyperthermia, which can cause severe brain damage16 through the activation of the 5-HT2A receptor. The early observation17 that the affinity of endogenous serotonin for the 5-HT1A receptors (K i =5.1 nM) is much higher than its affinity for 5-HT2A receptors (K i =420 nM) supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Serotoninový syndrom také může vést k mozkové smrti, snad mechanismem hypertermie. 34 Závěr VA-ECMO je velmi efektivní modalita u mnoha různých intoxikací. 19 Otrava tisem se zdá být vhodnou indikací.…”
Section: Diskuseunclassified